QR Code is a suggested template for an application In the Central Library at Damascus University (Damascus University Journal of arts and humanities sciences, 2022)
This study deals with the topic of the QR Code in the Central Library at the University of Damascus, in order to reach the goal of the study to present a concept for a proposed project "Applying the QR Code in the Central Library" as a model to be followed by libraries in government and private institutions. The study presented the concept of the QR Code. Code and its application requirements from the requirements for entering and producing the code and the requirements for the output and scanning of the QR Code. The areas of applying the QR Code were presented in libraries, in addition to its use by authors and publishers. The study presented in a practical framework a proposal for the application of the QR Code in the Central Library in The University of Damascus and the reasons for proposing the Central Library exclusively and the returns on applying the QR Code to the Central Library as well as the areas of applying the QR Code in the Central Library and how to apply the study arrived that the application of the QR CODE technology in the Central Library is an urgent necessity in the current era to increase Beneficiaries' satisfaction with the library services and to facilitate operations a Technical in the office of extracting and indexing.
Keywords: QR Code